2009
DOI: 10.1007/s10597-009-9219-2
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Individual Consumer–Provider Relationships Within Assertive Community Treatment

Abstract: The widespread adoption of assertive community treatment has resulted in a shift from an individual model to a team model of case management. The shift has had implications for individual relationships between case managers and consumers, but still little is known about how these relationships develop in teams. This exploratory mixed methods study looked at how case managers and consumers negotiate individual relationships within a team model. Quantitative methods identified high and low service intensity rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 30 publications
0
24
0
1
Order By: Relevance
“…The finding that providers believe older adults prefer to live in congregate settings is at odds with previous research that found people who have experienced homelessness would prefer to live independently in their own apartment (Tsemberis et al, 2004;Nelson et al, 2007) and is inconsistent with research that suggests most Americans express wanting to live independently regardless of age (Katz, 2011;Klinenberg, 2012). Although this may accurately reflect the preferences of some older adults who have experienced homelessness, provider misperception is also a likely explanation given documented discrepancies between the views of providers and homeless consumers (Stanhope and Matejkowski, 2010). An important distinction that neither the quantitative nor qualitative data differentiated between is that independent apartment living can be part of both single-site and scatter-site PSH (Tsemberis et al, 2004;Collins et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The finding that providers believe older adults prefer to live in congregate settings is at odds with previous research that found people who have experienced homelessness would prefer to live independently in their own apartment (Tsemberis et al, 2004;Nelson et al, 2007) and is inconsistent with research that suggests most Americans express wanting to live independently regardless of age (Katz, 2011;Klinenberg, 2012). Although this may accurately reflect the preferences of some older adults who have experienced homelessness, provider misperception is also a likely explanation given documented discrepancies between the views of providers and homeless consumers (Stanhope and Matejkowski, 2010). An important distinction that neither the quantitative nor qualitative data differentiated between is that independent apartment living can be part of both single-site and scatter-site PSH (Tsemberis et al, 2004;Collins et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, a qualitative study on 10 service users of mental health centres showed that changes in the allocated PMHP were experienced as setbacks in treatment, giving rise to negative feelings (Biringer, Hartveit, Sundfør, Ruud, & Borg, 2017). Even in team-based mental health services, the continuity of the individual relationship with one case manager seemed to play an important role for users' comfort level; users often expressed their preference for working with a particular case manager over others (Stanhope & Matejkowski, 2010). 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 F o r P e e r R e v i e w 11 Self-reports and questionnaires by 371 users of an Italian Community Mental Health service showed that users with the least education and those who spoke only Italian had a strong preference for a therapist of their own nationality (Lorefice & Borus, 1984).…”
Section: The Change Of the Pmhp: The Importance Of Continuity Of Carementioning
confidence: 99%
“…Til tross for at betydningen av relasjonen er viet økende oppmerksomhet i forskningen, foreligger det relativt få studier som har involvert brukere med alvorlige psykiske lidelser, og spesielt ikke de med både psykiske lidelser og rusproblemer (Denhov and Topor, 2012). Ikke minst mangler det fortsatt utdypende beskrivelser som viser hvorfor brukerne og ansatte opplever de generelle kvalitetene ved relasjonen og arbeidsformene som hjelpsomme og hva disse generelle kvalitetene består i. Det finnes også relativt få studier som ser på relasjonens betydning i desentraliserte tjenester utenfor den psykoterapeutiske behandlingsrammen eller institusjonskonteksten, selv om det er noen unntak (Hørberg, Brunt og Axelsson, 2004;O'Brian, 2001;Stanhope andMetejkowski, 2010, Sommer, Strand, Borg og Ness, 2013). I I denne artikkelen vil vi derfor beskrive betydningen av relasjonene slik de utvikler seg innenfor rammen av lokalbaserte tjenester, og utdype begrunnelsene til ansatte og brukere for at visse relasjonskvaliteter og arbeidsformer er hjelpsomme.…”
Section: Tidligere Studierunclassified